Structuring of ZnTiO3/TiO2 Adsorbents for the Removal of Methylene Blue, Using Zeolite Precursor Clays as Natural Additives - Jaramillo-Fierro, Ximena; González, Silvia; Montesdeoca-Mendoza, Fernando; Medina, Francesc (Nanomaterials (Basel, Switzerland), 2021)
Adsorption is an effective method of removing harmful pollutants from air and water. In the present study, zeolites prepared by sol-gel method from two Ecuadorian clays were combined with precursor clays and the ZnTiO3/TiO2 semiconductor for adsorbing methylene blue (MB) as a water contaminant. The synthesized compounds were characterized using powder X-ray diffraction, X-ray fluorescence, scanning electron microscopy, energy dispersive X-ray, and surface area measurement. These compounds were combined to form cylindrical extrudates of 0.2 cm (diameter) and 1.0 cm (length). The adsorption characteristics of the composites were measured using batch sorption studies as a function of pH, initial concentration, and contact time. The pseudo-second-order model and the Langmuir isotherm model were better suited to the adsorption process. The equilibrium state was achieved around 180 min of adsorption, and a pH of 7 was established as the optimal operating condition. The maximum adsorption values of the dye were obtained with the composites derived from G-Clay, whose average adsorption capacity was 46.36 mg g−1, in contrast with composites derived from R-Clay, whose average adsorption value was 36.24 mg g−1. The results reflect that synthesized composites could be used potentially for the removal of cationic dye from wastewater.